Symmetrical Optical Vector Analysis for High-Q Structures Based on Tandem Amplitude-Phase Modulation - Vasilets, A. A.; Misbakhov, R. Sh; Morozov, O. G.; Sarvarova, L. M.; Kuznetsov, A. A. (2021 Systems of Signals Generating and Processing in the Field of on Board Communications, 2021)
A symmetric optical vector analysis (OVA) based on amplitude-phase dual-band modulation with suppression of an optical carrier is proposed and numerically simulated. Accurate and stable frequency characteristics are achieved in it by the formation and minimization of such higher-order components in the probe radiation, the difference frequency of which does not coincide with the difference frequency of the two main first-order measuring components. Obtained high-quality characteristics were confirmed by numerical simulation of the developed OVA when analyzing the spectral parameters of an ultra-narrow-band fiber Bragg grating. The presented method is structurally simple, does not require the use of various generators to perform its main functions and monitoring functions, and can be used to characterize both selective fiber-optic structures and high-Q optical Fabry-Perot resonators, ring resonators of active and passive type, transparency windows of nonlinear crystals, etc.